2018
DOI: 10.1021/acs.energyfuels.8b01023
|View full text |Cite
|
Sign up to set email alerts
|

From Coreflooding and Scaled Physical Model Experiments to Field-Scale Enhanced Oil Recovery Evaluations: Comprehensive Review of the Gas-Assisted Gravity Drainage Process

Abstract: The gas-assisted gravity drainage (GAGD) process has been suggested to improve oil recovery in both secondary and tertiary stages through immiscible and miscible injection modes. In contrast to continuous gas injection and water-alternating gas, the GAGD process takes advantage of the natural segregation of reservoir fluids to provide gravity-stable oil displacement and improve oil recovery. In the GAGD process, the gas is injected through vertical wells at the top of the reservoir to formulate a gas cap that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…With the dramatic development of modern industry, the consumption of traditional fossil energy sources (e.g., coal, oil, and natural gas) is significantly increasing worldwide, resulting in the worries of energy shortage. Meanwhile, the excessive emission of greenhouse gases (e.g., carbon dioxide) in the atmosphere is triggering global climate change, via effects such as global warming. , Nowadays, achieving the means to increase the energy supply and concurrently reduce the emission of greenhouse gas has become an urgent problem for almost all countries. Fortunately, the development of unconventional reservoirs such as shale gas, known as a clean energy source with huge reserves and energy conversion rates, , greatly alleviates this problem and plans a new blueprint for the future world energy pattern.…”
Section: Introductionmentioning
confidence: 99%
“…With the dramatic development of modern industry, the consumption of traditional fossil energy sources (e.g., coal, oil, and natural gas) is significantly increasing worldwide, resulting in the worries of energy shortage. Meanwhile, the excessive emission of greenhouse gases (e.g., carbon dioxide) in the atmosphere is triggering global climate change, via effects such as global warming. , Nowadays, achieving the means to increase the energy supply and concurrently reduce the emission of greenhouse gas has become an urgent problem for almost all countries. Fortunately, the development of unconventional reservoirs such as shale gas, known as a clean energy source with huge reserves and energy conversion rates, , greatly alleviates this problem and plans a new blueprint for the future world energy pattern.…”
Section: Introductionmentioning
confidence: 99%
“…The CO 2 -EOR contains different methods such as CO 2 -WAG, continuous CO 2 injection, CO 2 huff-n-puff (H-n-P), and gas-assisted gravity drainage (GAGD). , Furthermore, studies have been conducted to assess the performance of CO 2 -EOR techniques in oil-bearing reservoirs that showed that continuous CO 2 injection during CO 2 -EOR is highly effective for oil displacement and viscosity reduction. , However, this continuous CO 2 injection can cause CO 2 breakthrough that is induced by gravity segregation, thereby causing viscosity fingering and permeability reduction because of inorganic and asphaltene deposition . The GAGD is presented as a powerful CO 2 -EOR technique to improve oil recovery because of the density difference between the injected gas and the crude oil. , The main advantage of GAGD is the huge volume of CO 2 that can be injected into the subsurface formation, which leads to cutting down the large-scale emissions of CO 2 into the atmosphere and boosts the volumetric sweep efficiency. , The basic idea behind GAGD is to inject gas vertically to form a gas cap, then utilize gravity segregation to drive oil and water out of the reservoir by employing situated horizontal wells to extract the oil.…”
Section: Introductionmentioning
confidence: 99%
“…The GAGD is presented as a powerful CO 2 -EOR technique to improve oil recovery because of the density difference between the injected gas and the crude oil. , The main advantage of GAGD is the huge volume of CO 2 that can be injected into the subsurface formation, which leads to cutting down the large-scale emissions of CO 2 into the atmosphere and boosts the volumetric sweep efficiency. , The basic idea behind GAGD is to inject gas vertically to form a gas cap, then utilize gravity segregation to drive oil and water out of the reservoir by employing situated horizontal wells to extract the oil. In contrast, the presence of methane in the reservoir will cause to reduce the dissolved CO 2 in the crude oil, which results in reducing oil swelling . Also, decrease in oil viscosity occurs when CO 2 is saturated with the oil reservoir at high pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Theoretical research and eld practice has demonstrated that GAGD can inhibit viscous ngering and increase swept volume and ultimate recovery factor. [6][7][8][9] GAGD is inuenced by many factors, [10][11][12][13] including heterogeneity, wettability, and water saturation of the reservoir, uid property, gas injection rate, and oil recovery factor. Dominant seepage zones or dominant seepage paths frequently occur in the reservoirs with high heterogeneity, leading to early gas breakthrough and sweep efficiency reduction during CGI or WAG.…”
Section: Introductionmentioning
confidence: 99%